Child poverty in comparative perspective: Assessing the role of family structure and parental education and employment - Janet C. Gornick; Markus Jäntti (Luxembourg Income Study (LIS), 2011)
This paper draws on the Luxembourg Income Study (LIS) microdata to paint a portrait of child poverty across a diverse group of countries, as of 2004-2006. We will first synthesize past LIS-based research on child poverty, focusing on studies that aim to explain cross-national variation in child poverty rates. Our empirical sections will focus on child poverty in 20 high- and middle-income countries - including three Latin American countries, newly added to LIS. We will assess poverty among all households and among those with children, and using multiple poverty measures (relative and absolute, pre- and post- taxes and transfers). We will assess the effects of crucial micro-level factors - family structure, educational attainment, and labor market attachment - considering how the effects of these factors vary across counties. Finally, we will analyze the extent to which crossnational variation in child poverty is explained by families' characteristics and/or by the effects of (or returns to) those characteristics. Those returns encompass both market and state-generated income.
Keywords: 330